Видение образа Сократа в творчестве К. Варналиса - Корнийко, К.В.; Бридко, Т.В. (Культура народов Причерноморья, 2014)
Данная статья посвящена изучению и анализу образа Сократа, олицетворяющего собой
древнегреческую философию. В статье представляется обзор произведений, формирующих видение
образа Сократа его учениками и современными авторами. Подана стаття присвячена вивченню та аналізу образу Сократа, який уособлює собою
давньогрецьку філософію. У статті надається огляд творів, які формують бачення образу Сократа
його учнями і сучасними авторами. The work of Greek authors are one of the less researched areas in literary studies. Therefore this
article is devoted to the study and an analysis of the image of Socrates. He is one of the most prominent figures
of his era. A philosopher who had a great impact on his society as well as on the whole humankind, Socrates’
ideas have enriched our culture and greatly influenced our history. The article provides an overview of the works
devoted to the description of his life and teaching, forming the vision of Socrates by his disciples as well as by
modern authors. The philosopher is given a prominent place in the history of philosophy, ethics and morality.
For almost three thousand years his ideas have been capturing the minds of mankind, and his dialogues
represent a philosophical technique that step by step allows finding out the truth. The ideas that he preached
(morality, honesty, patriotism) are those vital qualities, which will always be the same for forming an ideal
society. Socrates' battle with dishonour, lies and pseudo patriotism are burning even in nowadays' society. The
authors believe that by studying Socrates, we can understand the time and political events that occur in our life
easier. It would be very interesting and useful to continue the following research in the homeland of Socrates in
order to discover some new material for a usual Ukrainian linguist or philosopher.